2013
DOI: 10.3390/en6083901
|View full text |Cite
|
Sign up to set email alerts
|

Use of LCA as a Tool for Building Ecodesign. A Case Study of a Low Energy Building in Spain

Abstract: This paper demonstrates how to achieve energy savings in the construction and operation of buildings by promoting the use of life cycle assessment techniques in the design for new buildings and for refurbishment. The paper aims to draw on the application of a specific methodology for low energy consumption, integrated planning, environmental performance evaluation of buildings, and design for sustainability and LCA techniques applied to buildings. The ENergy Saving through promotion of LIfe Cycle assessment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 36 publications
1
23
0
5
Order By: Relevance
“…The ecodesign of products is based on the integration of environmental aspects into product design and development, with the aim of reducing adverse environmental impacts throughout a product's life cycle (ISO/TR, ). A literature survey revealed that the term “ecodesign” (together with “sustainable design”) was established for expression of improving the environmental performance of buildings (Zabalza, Scarpellini, Aranda, Llera, & Jáñez, ). In this paper ecodesign is used because it is more frequently used in the construction sector and is consistent with the ISO 14000 series (ISO, ).…”
Section: Introductionmentioning
confidence: 99%
“…The ecodesign of products is based on the integration of environmental aspects into product design and development, with the aim of reducing adverse environmental impacts throughout a product's life cycle (ISO/TR, ). A literature survey revealed that the term “ecodesign” (together with “sustainable design”) was established for expression of improving the environmental performance of buildings (Zabalza, Scarpellini, Aranda, Llera, & Jáñez, ). In this paper ecodesign is used because it is more frequently used in the construction sector and is consistent with the ISO 14000 series (ISO, ).…”
Section: Introductionmentioning
confidence: 99%
“…The creation of tools that include LCA and optimization algorithms offers potential for technological innovation in structure through the selection, over the whole life cycle, of the best alternatives [23]. Up until now a NZEB-compliant methodology solving all the problems of the complex interplay of energy production and consumption in buildings was not available [24,25]. Moreover, the proposed DSS can be applied to general buildings and use cases: residential and industrial areas, agricultural systems, buildings including offices, manufacturing systems, university campuses, etc.…”
Section: Introductionmentioning
confidence: 99%
“…According to National Economical Industry Classification (GB/T4754-2012), the building industry includes: construction of buildings, civil engineering, and renovation and decoration four categories. Based on the previous studies [29,[37][38][39][40][41] and the IPCC method of carbon emission inventories [2], we build the CO 2 emission calculation model for China's building industry. The CO 2 emission calculation of building industry includes two parts: first part is the direct CO 2 emissions and second part is indirect CO 2 emissions shown in the following equation:…”
Section: Italy and Europementioning
confidence: 99%
“…Based on previous studies [17,29,[37][38][39][40], carbon emissions from the building industry should include two parts: one is direct carbon emission from direct fossil fuel combustion in building industry and the other is indirect carbon from building material consumption.…”
Section: Estimation Of Co2 Emissions From China's Building Industrymentioning
confidence: 99%
See 1 more Smart Citation